Prognostic Impact of Menopausal Hormone Therapy in Breast Cancer Differs According to Tumor Characteristics and Treatment - Godina, Christopher; Ottander, Erik; Tryggvadottir, Helga; Borgquist, Signe; Isaksson, Karolin; Jernström, Helena (Frontiers in Oncology, 2020)
This study investigated how a history of menopausal hormone therapy (MHT) impacts clinical outcomes overall and in different subgroups of breast cancer patients. The study included 814 primary breast cancer patients aged ≥50 years in Sweden (2002–2012) with follow-up until 2016. Associations between patient- and tumor characteristics, recurrences, and overall survival were analyzed in relation to MHT. After a median follow-up of seven years, 119 recurrences and 111 deaths occurred. Ever MHT (n=433, 53.2%) was associated with a lower BMI, frequency of alcohol abstinence, and histological grade, higher frequency of oral contraceptive use, and lobular cancer. Overall, MHT was not associated with prognosis, but there were significant effect modifications by estrogen receptor (ER) status, node status, main histological type, and aromatase inhibitor (AI) treatment on recurrence-risk (all Pinterations≤0.017). MHT conferred an increased recurrence-risk in patients with ER- tumors, adjusted Hazard Ratio (HRadj) 3.99 (95% Confidence Interval (CI) 1.40–11.33), in node-negative patients HRadj 1.88 (95% CI 1.11–3.17), and in non-AI-treated patients HRadj 1.81 (95% CI 1.01–3.24), but decreased recurrence-risk in AI-treated patients HRadj 0.46 (95% CI 0.25–0.84) and in patients with lobular cancer HRadj 0.15 (95% CI 0.04–0.64). MHT was associated with lower risk of death in node-positive patients HRadj of 0.48 (95% CI 0.27–0.86) and in AI-treated patients HRadj of 0.41 (95% CI 0.22–0.77), but not in other patients (both Pinterations≤0.027). A history of MHT may have prognostic value for certain subgroups of breast cancer patients such as AI-treated or node-negative patients.